2023
DOI: 10.1101/2023.04.18.537104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single inactivating amino acid change in the SARS-CoV-2 NSP3 Mac1 domain attenuates viral replication and pathogenesisin vivo

Abstract: Despite unprecedented efforts, our therapeutic arsenal against SARS-CoV-2 remains limited. The conserved macrodomain 1 (Mac1) in NSP3 is an enzyme exhibiting ADP-ribosylhydrolase activity and a possible drug target. To determine the therapeutic potential of Mac1 inhibition, we generated recombinant viruses and replicons encoding catalytically inactive NSP3 Mac1 domain by mutating a critical asparagine in the active site. While substitution to alanine (N40A) reduced activity by ~10-fold, mutations to aspartic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…These results indicate that Mac1 enzyme activity may be important for countering IFN-γ activity during a SARS-CoV-2 infection. In addition, a recent preprint also found that an N1062D mutation, which significantly reduced enzyme but not binding activity, was also more sensitive to IFN-γ pretreatment that WT virus ( 47 ). These results demonstrate that IFN-γ pretreatment of Calu-3 cells more effectively impedes the replication of SARS-CoV-2 Mac1 mutant viruses compared to WT virus, likely due to the loss of Mac1 ADP-ribosylhydrolase activity.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that Mac1 enzyme activity may be important for countering IFN-γ activity during a SARS-CoV-2 infection. In addition, a recent preprint also found that an N1062D mutation, which significantly reduced enzyme but not binding activity, was also more sensitive to IFN-γ pretreatment that WT virus ( 47 ). These results demonstrate that IFN-γ pretreatment of Calu-3 cells more effectively impedes the replication of SARS-CoV-2 Mac1 mutant viruses compared to WT virus, likely due to the loss of Mac1 ADP-ribosylhydrolase activity.…”
Section: Resultsmentioning
confidence: 99%